Erratum: THAÍS TEIXEIRA CONEGIRO, ISA LUCIA DE MORAIS, LIONIZIA GOYÁ, ARTHUR DE SOUZA SOARES & GUILHERME MEDEIROS ANTAR (2026) The rediscovery of Hyptis argentea (Lamiaceae: Hyptidinae) in the Brazilian Cerrado after 70 years. Phytotaxa 750 (4): 291–300. - Conegiro, Thaís Teixeira; Morais, Isa Lucia De; Goyá, Lionizia; Soares, Arthur De Souza; Antar, Guilherme Medeiros (Phytotaxa, 2026)
N/A